Stenosing tenosynovitis of the abductor pollicis longus muscle in dogs - Grundmann, S.; Montavon, P. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
Chronic lameness of the forelimb with a firm swelling at the medial aspect of the antebrachiocarpal joint can be caused by a tenosynovitis of the abductor pollicis longus muscle. Connective tissue proliferation leads to stenosis of the synovial sheath. The patients show pain in hyperflexion of the carpus. Radiographically, proliferative bone reactions at the distal radius can be found in advanced cases of the disease. If the results of medical treatment by injection of corticosteroids in the area of the synovial sheath are not successful, good results can be achieved by surgical release of the tendon. Based on 10 cases examined, aetiology, clinical findings and therapy are discussed and compared with de Quervain’s tenosynovitis in man.Lameness due to tenosynovitis of the abductor pollicis longus muscle is reported and findings and therapy of ten animals is discussed.
Keywords: Tenosynovitis; abductor pollicis longus muscle; dog